Re-Strategizing NATO’s Roles as Transatlantic Security Alliance in Europe Post Russia-Ukraine Conflict - Lalu Ladeva Alfusa'idu Karman (Mandala: Jurnal Ilmu Hubungan Internasional, 2023)
The condition of Europe’s geopolitical stability has been hit hard since the early 2022. The war between Russia and Ukraine has prevail and proven to disrupt the capacity and capability of intra-regional bodies within Europe. As the fight is still going on and war has not declared to be over there are obstacles to analyze what will the region be after the conflict is ended especially on how will the Russia repowered themselves and the action taken by EU and NATO to respond to such threat. This research will attempt to scrutinize and underpin NATO’s important job and roles as the guardian in Europe amidst the current geopolitical instability within the region including its alliance with European Union. The perspectives from Balance of Threat and Security Alliance Theory, is the tools to analyze what lies ahead in the importance of NATO for the region. This research uses the data analysis methods and collecting data using secondary data from multiple sources such as journals, government websites, articles, and books. Further, this research limits the scope into the relationship between NATO and European Union and will perceive the future of what the region might looks like after the conflict ends. Keywords: NATO, European Union, Security Alliance, Russia-Ukraine